Human security and its Multidimensionality - Cruz, Edwin (2023)
This article aims to analyze the concept of human security and its multidimensionality in the international context according to the historical evolution of security; having as a starting point the various instances promoted by the United Nations and by different countries since 1994, which is characterized by its universal nature, centered on people and interdependence, focused on conflict prevention and cooperation. Since the publication of the 1994 Human Development Report on human security, national human development reports on human security have been produced. These reports have shown how the concept of human security can be contextualized and used to promote more appropriate responses to the particular types of insecurity that affect each country. It is also worth noting the Declaration on Security in the Americas, approved in October 2003 by the OAS. This Declaration recognizes that the conditions of human security depend on respect for the dignity of persons, human rights and fundamental freedoms. The concept has generated significant debate at the United Nations and other bodies. However, there is still no broad consensus in the UN, nor in the academic world about it. This work provides an analysis of the conceptual evolution of human security from the various contributions of the United Nations, as well as a state of the art on human security.